Developmental idealism and cultural extinction in the selected works of Chuma Nwokolo - Nkeokelonye, Adaobi (2020)
To be developed, countries in Africa must comply with a development agenda, adopting the beliefs and values that inform the ideals of development. With strong links to modernization, the ideologies underpinning development as well as their impact and adoption in Africa have undergone critical studies. The impact of development is contingent on a people’s culture, and thus can potentially be a threat that can trigger cultural extinction. The relationship between development and culture, and its potential link to cultural extinction arising from conflict of values is largely unexplored. Literary works produced within the African region have captured processes of culture and social change, depicting development issues in ways that are intellectually relatable. The struggle of minority people to sustain their culture in the face of the pressures of development is also captured in literary works. Notwithstanding, a sparsity of studies on literature that have substantively covered these phenomena and the remedial measures for addressing it, is observed. My study attempts to address these gaps by examining contemporary African literature for insight. Through a synthesis of theories and concepts which includes Arland Thornton’s theory of Developmental Idealism and the concept of Cultural Extinction this study explores the intersections of development with the occurrence of cultural extinction. Eric Yamamoto’s four-fold framework for inter-racial justice (recognition, reconstruction, responsibility and reparation), is also adopted to explore redress and remedial strategies adopted for eclipsing culture. The thematic relevance of works produced by Nigerian author Chuma Nwokolo justifies the selection of four novels from his body of work: Extinction of Menai (2018), One More Tale for the Road (2003), Diaries of a Dead African (2003) and The Ghost of Sani Abacha (2012). Textual analysis remains the central methodology of cultural studies. A systematic analysis of texts from the selected works of Chuma Nwokolo in the light of the theories and concepts employed reveal the representations of the values of developmental idealism across the four works. While cultural extinction is evidenced across the selected works of Chuma Nwokolo, rather than causality, the analysis establishes mostly that the ideational force of developmental idealism has a relationship of correlation to cultural extinction. Eric Yamatoto’s four component framework; recognition, reconstruction, responsibility and reparation, are found to be most applicable to the cultural remedial and redress approaches adopted across the four works only at the intra-cultural level. It is expected that the outcome of this study will inform policies, programmes and interventions of institutions that focus on achieving cultural sustainability across the world. Most importantly, it will inform remedial approaches for cultural revitalization.